2022
DOI: 10.1007/s00066-022-01977-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum lactate dehydrogenase predicts brain metastasis and survival in limited-stage small cell lung cancer patients treated with thoracic radiotherapy and prophylactic cranial irradiation

Abstract: Background: Small cell lung cancer (SCLC) is characterized with high risk of brain metastasis and poor survival. This study aimed to assess the prognostic role of LDH in limited stage small-cell lung cancer (LS-SCLC) treated with thoracic radiotherapy (TRT) and prophylactic cranial irradiation (PCI).Methods: This study retrospectively evaluated 197 consecutive patients who underwent TRT and PCI for LS-SCLC between November 2005 and October 2017. Both pretreatment and maximal serum LDH levels (mLDH) during trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…ECOG PS was the patient characteristic with the strongest association with survival, providing additional evidence that ECOG PS is an important predictor of survival in patients with lung cancers ( 1 , 34 , 39 ). OS estimates were lower in patients with characteristics traditionally associated with poor prognosis (high LDH, abnormal sodium, and low hemoglobin) ( 35 38 , 40 ), confirming the results of our previous analysis in the earlier version of this cohort study ( 34 ). To our knowledge, this is the most current population-based study to comprehensively evaluate treatment patterns and clinical outcomes in Canadian patients with LS-SCLC treated with CT ± RT.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…ECOG PS was the patient characteristic with the strongest association with survival, providing additional evidence that ECOG PS is an important predictor of survival in patients with lung cancers ( 1 , 34 , 39 ). OS estimates were lower in patients with characteristics traditionally associated with poor prognosis (high LDH, abnormal sodium, and low hemoglobin) ( 35 38 , 40 ), confirming the results of our previous analysis in the earlier version of this cohort study ( 34 ). To our knowledge, this is the most current population-based study to comprehensively evaluate treatment patterns and clinical outcomes in Canadian patients with LS-SCLC treated with CT ± RT.…”
Section: Discussionsupporting
confidence: 88%
“…Patient characteristics included current age, age at diagnosis, sex, smoking status, stage of disease at diagnosis, laboratory test results at diagnosis, and ECOG PS at diagnosis. Key parameters of laboratory testing included levels of LDH, sodium, and hemoglobin, which have been identified as important prognostic factors in LS-SCLC ( 35 38 ). Laboratory values in our database were acquired prior to cycle 1 and CT typically starts within 1-2 weeks of clinician assessment.…”
Section: Methodsmentioning
confidence: 99%
“…At present, there are many risk factors for BM of SCLC reported worldwide, such as LDH, 14 CEA, 15 gastrin releasing peptide precursor (ProGRP) 16 and PLT, 17,18 HGB 18 , neutrophil to lymphocyte ratio (NLR), [19][20][21] monocyte-lymphocyte ratio (MLR), 21 prognosticnutrition index (PNI), 21 TNM stages, 15,16,18,19,[22][23][24][25][26][27] lymphovascular invasion or not, 23 radical surgery or not, 22 concurrent chemotherapy (CCRT) or not, 21 response to chemotherapy, 28 weight loss, 28 time to thoracic radiotherapy, 16,19 chemotherapy cycles, 16,19 dose of thoracic radiotherapy, 29 size of primary tumour, 25 segmentation method of thoracic radiotherapy, 26 age, 27 gender, 18,27 and so forth. However, only three of these studies established a predictive model for BM in SCLC; it is expected that prediction models for these factors of high risk of BM can be subsequently established and verified both internally and externally.…”
Section: Discussionmentioning
confidence: 99%
“…According to the current guidelines, concurrent platinum-based radiochemotherapy (RCT) with subsequent prophylactic whole-brain irradiation (WBI) is regarded as standard treatment for SCLC patients with limited disease [ 8 , 9 ]. At this stage of disease, a recent study has shown that in patients treated with thoracic RT and WBI, intratherapeutic maximal serum lactate dehydrogenase levels are predictive of possible brain metastasis and survival [ 10 ].…”
Section: Introductionmentioning
confidence: 99%